FAKTOR OKUPASIONAL YANG BERKAITAN DENGAN INFARK MIOKARD AKUT PADA DEWASA USIA KERJA: TINJAUAN NARATIF TERSTRUKTUR: OCCUPATIONAL FACTORS ASSOCIATED WITH ACUTE MYOCARDIAL INFARCTION IN WORKING-AGE ADULTS: A STRUCTURED NARRATIVE REVIEW - Airin Farah Tsabita Batubara; Saiful Batubara; Muhammad Diah; Bless Dova Fransza Andrew Sihujur Hutabarat; Ramadhan Bestari (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
Acute myocardial infarction (AMI) remains a major cause of mortality, disability, and healthcare utilisation worldwide. In addition to conventional cardiovascular risk factors, workplace exposures and employment conditions may influence AMI occurrence and subsequent outcomes. This structured narrative review synthesised evidence on occupational factors associated with AMI among working-age populations. A focused PubMed search was conducted on 2 February 2026 for full-text English-language articles published from January 2010 to January 2026. Of 108 records identified, eight cohort studies met the eligibility criteria and formed the core evidence set. Methodological quality was assessed using the JBI Critical Appraisal Tool for Cohort Studies, and findings were synthesised by exposure domain. Outcomes included first-time AMI, coronary heart disease outcomes explicitly including AMI, and mortality or prognosis following AMI. Occupational diesel engine exhaust exposure showed the most consistent positive association with incident AMI, whereas findings for respirable crystalline silica or quartz were inconsistent. Associations involving night work, shift work, and travelling work were generally modest or limited to specific subgroups. Occupational physical activity was not consistently associated with AMI, while unstable employment was associated with higher 2-year mortality following AMI. Heterogeneity in exposure definitions, assessment methods, and outcome classification limited direct comparison and causal interpretation. AbstrakInfark miokard akut (IMA) tetap menjadi penyebab utama kematian, disabilitas, dan pemanfaatan layanan kesehatan di seluruh dunia. Selain faktor risiko kardiovaskular konvensional, pajanan dan kondisi kerja dapat memengaruhi kejadian IMA serta luaran setelahnya. Tinjauan naratif terstruktur ini bertujuan menyintesis bukti mengenai faktor okupasional yang berkaitan dengan IMA pada populasi usia kerja. Pencarian terfokus dilakukan di PubMed pada 2 Februari 2026 untuk artikel lengkap berbahasa Inggris yang diterbitkan antara Januari 2010 dan Januari 2026. Dari 108 rekaman yang ditemukan, delapan studi kohort memenuhi kriteria dan dimasukkan sebagai bukti inti. Kualitas metodologis dinilai menggunakan JBI Critical Appraisal Tool for Cohort Studies, dan temuan disintesis berdasarkan domain pajanan. Luaran mencakup kejadian pertama IMA, penyakit jantung koroner yang secara eksplisit mencakup IMA, serta mortalitas atau prognosis setelah IMA. Pajanan diesel engine exhaust menunjukkan hubungan positif paling konsisten dengan kejadian IMA, sedangkan temuan mengenai respirable crystalline silica atau quartz tidak konsisten. Hubungan kerja malam, kerja bergilir, dan travelling work umumnya moderat atau terbatas pada kelompok tertentu. Aktivitas fisik okupasional tidak menunjukkan hubungan yang konsisten, sedangkan ketidakstabilan pekerjaan berkaitan dengan mortalitas dua tahun yang lebih tinggi setelah IMA. Heterogenitas pajanan, metode penilaian, dan definisi luaran membatasi perbandingan langsung dan kesimpulan kausal.